Comparison of Fish between Artificial Seagrass and Artificial Reefs in Turun Aban Beach Sungailiat, Regency of Bangka - Andre Faizer; Wahyu Adi; Umroh Umroh (Journal of Aquatropica Asia, 2016)
TurunAban Beach has fringing reefs along the shoreline, where habitat of reef and fish are associated. A transplantation purpose is for the preservation of coral reef ecosystems so that organisms can live sustainably. This study was conducted on April and May 2015, which aims to find out the diversity of fish on artificial reefs with artificial seagrass and comparing the abundance of fish in artificial reefs with of artificial seagrass. Based on this study, the method used in this study is a casestudy. The fish found along transect lines were observed in term of species and amount. Data diversity, uniformity, and dominance were analyzed descriptively. The result showed the diversity index (H ') on artificial reefs was 1,29, the value can be categorized as being moderately populated. Diversity index on a coral artificial reef greater than in artificial seagrass (1,21) with the category of the population being moderately populated, the abundance of fish found highly in artificial seagrass artificial (38 individue/m2) fish, while in artificial reefs were found 36 individue /m2